Mobile health architecture for health-care information delivery: case study: a breast cancer awareness mobile application (PINK RIBBON) - Gakinya, Carolyne Wariara (Strathmore University, 2017)
Mounting interest in the field of m-Health—the provision of health-related services via mobile communications—can be traced to the evolution of several interrelated trends. In many parts of the world, including the developed and the developing countries, access to health care is a basic need yet this is not a reality to a large section of the population in these countries. These challenges normally arise as a result of high costs of healthcare, few medical personnel compared to the patients to be served and few medical facilities. In the developing countries, other challenges such as poor infrastructure, poor policy implementation, literacy levels and language barrier are stumbling blocks to access health care services. Yet in these same places, the explosive growth of mobile communications over the past decade offers a new hope for the promotion of quality healthcare. This reliable technology helping to bridge the ‘digital divide’ gap. There is a growing body of evidence that demonstrates the potential of mobile communications to radically improve healthcare services—even in some of the most remote and resource-poor environments. The research explores the usage of m-Health applications in developing countries especially Kenya as well as the health needs to which m-Health can be applied. It determines the design requirements of an m-Health architecture that can be used both as an informative and educative tool to the masses. This architecture is implemented by analysing, designing and testing a primary m-Health application that can be used to raise awareness about Breast Cancer as well as assist Community Health Workers to educate the general public about other general health related information. In conclusion some key design, business and technical requirements that need to be considered are suggested.
Thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Mobile Telecommunication and Innovation at (MSc.MTI) at Strathmore University
Keywords: M-Health; Healthcare Information delivery